INTEGRATING EXTENDED THEORY OF PLANNED BEHAVIOR AND NORM ACTIVATION MODEL TO EXAMINE THE FACTORS AFFECT MANAGERS INTENTION TO RECYCLE HOSPITAL WASTE - Suriati Deraman; Lee Khai Loon; Puteri Fadzline Muhamad Tamyez (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Environmental pollution is a serious global issue that has received increasing attention from scholars, policymakers, regulators, environmental activists, and the public. The healthcare industry does not run away from contributing problems to the environment. Therefore, managers are seen as important people in overcoming this problem. The purpose of this study to investigate managers intention to recycle hospital waste in their organization. This study integrates the theory pf planned behaviour and Norm activation model to conceptualize the factors of managers intention to recycle hospital waste. Standardized structured questionnaires are distributed through email where the targeted respondent must be ranked manager position and above with medical background. A total of 181 respondents usable were collected and data analyse by partial least square structural equation model (PLS-SEM). This study revealed that managers intention is significantly affect by the attitudes towards recycling intention, ascription responsibility and personal norm. However, the finding on the factor awareness of consequences and subjective norms are not supported in affecting the intention to recycle hospital. A total 6 hypotheses was tested and four hypotheses were accepted and two hypotheses rejected. The findings of this study provide important theoretical and practical implications for scholars, managers, and policymakers.